Eco-Pesantren and Islamic Environmental Education: A Phenomenological Study in Boarding Culture - Adzillah, Salsabila Nur Imatul; Ratnasari, Dwi; Jannata, Taufan; Adzibah, Salsabila I'tilaful; Dwinandita, Audrey Shafia (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2025)
Purpose – This study investigates why formal eco-pesantren cleanliness regulations at MAN 2 Yogyakarta have not consistently translated into students’ everyday ecological behaviour. While Islamic environmental education has institutionalized cleanliness policies, a gap persists between normative rules and lived practice. This research addresses that gap by examining how boarding culture shapes, mediates, and is experienced in students’ cleanliness practices and ecological awareness. The principal argument advanced is that ecological behaviour in Islamic boarding schools is not solely regulation-driven but is constructed through layered meaning-making within micro-level room culture. Design/methods– A qualitative phenomenological approach was employed to capture students’ lived experiences. Fourteen purposively selected participants were involved, comprising one boarding supervisor, one musrifah, and twelve students representing five boarding rooms. Data were collected through in-depth semi-structured interviews, participatory naturalistic observation conducted over a three-month period, and document analysis of institutional cleanliness policies. Data analysis followed a systematic coding procedure open, axial, and selective coding to identify thematic structures of ecological awareness formation. Findings – The findings reveal a three-layered developmental pattern of ecological awareness. First, most participants (12 of 14) initially framed cleanliness pragmatically in terms of personal comfort and avoidance of sanctions. Second, 10 participants demonstrated an emerging sense of collective responsibility shaped by shared room dynamics and peer regulation. Third, a smaller subset (4 participants) articulated ecological practice as religiously meaningful, conceptualizing cleanliness as amanah, adab, and an expression of the human role as khalifah. These results confirm that Islamic environmental education becomes effective when formal regulations are integrated with students’ lived experiences and room-based cultural interactions. Keyword: eco-pesantren; Islamic environmental education; ecological awareness; boarding culture; phenomenological